2024
DOI: 10.1038/s41398-024-02807-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and immunological effects of yoga compared to memory training in older women at risk for alzheimer’s disease

Adrienne Grzenda,
Prabha Siddarth,
Michaela M. Milillo
et al.

Abstract: Subjective cognitive decline (SCD) and mild cognitive impairment (MCI) accompanied by cerebrovascular risk factors (CVRFs) are known to increase the risk of developing dementia. Mind-body practices such as yoga and meditation, have been recognized as safe techniques with beneficial effects on cognitive functions in older adults at risk for cognitive decline. We conducted a randomized, controlled trial to assess the efficacy of Kundalini yoga training (KY) compared to memory enhancement training (MET) on mood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…During the subsequent stage, additional papers were excluded based on predefined criteria that did not feature KY as the primary intervention. Five RCTs meeting all inclusion criteria were deemed suitable for review, involving 215 participants [19][20][21][22][23]. The summary characteristics of the studies are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the subsequent stage, additional papers were excluded based on predefined criteria that did not feature KY as the primary intervention. Five RCTs meeting all inclusion criteria were deemed suitable for review, involving 215 participants [19][20][21][22][23]. The summary characteristics of the studies are outlined in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eyre et al and Grzenda et al reported significant improvements in depressive symptoms and resilience in the KY groups compared to the control groups [19,20]. These mood improvements were sustained over the 24-week follow-up period.…”
Section: Mood and Psychological Outcomesmentioning
confidence: 89%
See 3 more Smart Citations